INDIA’S TRIBES: THEIR ECONOMIC AND SOCIOECONOMIC ADVANCEMENT VIA ART - Thosar, Apurva; Sharma, Jitendra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The guardians of nature are the tribes. Most of India’s tribal population—92 per cent—lives in arid, hilly, or wooded regions. Their main sources of nutrition are minor forest products and agriculture. The primary areas of India where the tribal population resides are the central region, the middle belt, and the northeastern states. India’s tribal arts are steeped in history and have developed unique methods and traits. Many people acknowledge various tribes as autonomous creative forms with unique visual value. Everything that contributes to a creative creation’s uniqueness, such as composition, line, colour, texture, and rhythm. This study paper examines in-depth the socioeconomic growth of Indian tribes via art. The Indian government need to devise a unique strategy with the primary goal of encouraging the overall development of tribes being the preservation and integration of these ethnic communities.